A SCIENTIFIC REVIEW ABOUT SEXUAL AND REPRODUCTIVE RIGHTS ON COLOMBIA, 1994-2004 - Ospina Muñoz, Doris Elena; Castaño López, Rosa (Investigación y Educación en Enfermería, 2009)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Study carried out between July 2005-July 2008, started from COLCIENCIAS’ National Base of Products (X-ACTA). Objective: to gather knowledge and critical reflections about knowledge accumulated in the categories associated to sexual and reproductive rights in Colombia, 1994-2004. Methodology: we consult XACTA using descriptor. The articles are organized in three groups according to where they are published: national indexed journal (T1), national non indexed journal (T2), foreign journal (T3). We build thematic categories and carry out understanding readings. Results: we obtain a total of 123 articles distributed in this way: 32 for gender, justness and education; 30 in women’s health. Five in homosexuality and prostitution, two for men’s health, 22 for citizenship and education; 13 for health system and human rights, three in children´s rights, eight for differential of gender and eight for voluntary interruption of the pregnancy. Qualitative ethnographies predominate in the studies. The relationship author-article is of one-to-one, that can indicate low specialization level in the workspace, but also many researchers interested in them. Conclusion: the production volume on: justness, citizenship and education, sexual diversity and children rights show theoretical concern and discursive advances that should be integrated to the sexual and reproductive health policy. There is abundant research production, especially qualitative and formative approach. However, we need to improve methodological designs, qualify both training and formation process of health professionals and embody the gender perspective.